(-2x+8)=0

Simple and best practice solution for (-2x+8)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-2x+8)=0 equation:


Simplifying
(-2x + 8) = 0

Reorder the terms:
(8 + -2x) = 0

Remove parenthesis around (8 + -2x)
8 + -2x = 0

Solving
8 + -2x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + -8 + -2x = 0 + -8

Combine like terms: 8 + -8 = 0
0 + -2x = 0 + -8
-2x = 0 + -8

Combine like terms: 0 + -8 = -8
-2x = -8

Divide each side by '-2'.
x = 4

Simplifying
x = 4

See similar equations:

| (3x+6)=6 | | (-2-x)=9 | | (x)=-0.65x^3+0.57x^2+56.68x+3104 | | (4x-2)=-6 | | 3.5(6x-2)=3.5 | | 5(-3.1x+6.9)=-3.5 | | 5z=2.3+4.2 | | x*20/3=5/6 | | -0.3(3+8x)=0.9 | | -3(2x+1.2)=-1 | | 12/19=-4z | | 0=-0.5x^2+7x-20 | | 8x+82x=80 | | 9=3y+37+4y | | 5/2t=-7/3 | | x=-0.5x^2+7x-20 | | -12x^2+42x-20=0 | | -(2x-10)-1=2 | | 3a^2+27b^2+5c^2-18ab-30c=-237 | | 12x^2-42x-20=0 | | 72+13m=293 | | -38=5u+17 | | 24x-26x=8-10 | | 14x^2=18-36x | | (3+3i)-(-2-i)=0 | | 7/3*t=-6/5 | | 15h^2-23h-28=0 | | 7/3t=-6/5 | | z^2+20z+96=0 | | 8x+7z=6+7y | | 12x^2+42x+20=0 | | s^2+6s-40=0 |

Equations solver categories